The Determinants of Environmental Quality in Indonesia - Peris Frengki Butarbutar; Candra Fajri Ananda; Ferry Prasetya (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2023)
Purpose This research analyzes the determinants of environmental quality in 32 Indonesian provinces in the period between 2013-2019. Design/methodology/approach This research method used an ordinal logistic regression analysis approach where the dependent variable consists of cumulative predicate categories based on the EQI assessment interval as determined by the Ministry of Environment and Forestry. Findings This study finds that the per capita GDRP and poverty have positive and significant effects on the Environmental Quality Index. However, The Human Development Index and expenditures in environmental and forestry functions have negative and significant effects. Research limitations/implications Based on the findings, the local and central government, through the Ministry of Environment and Forestry in cooperation with business people required to conduct the Environmental Impact Analyses, should participate in PROPER. Originality/value This study will show how the inter-components of economic development, social development, income and expenditure on environmental and forestry functions affect each category of the Environmental Quality Index (EQI) predicate.